Chemical manipulation of plant water use. Issue 3 (1st February 2016) - Helander, Jonathan D.M.; Vaidya, Aditya S.; Cutler, Sean R.
Graphical abstract: Abstract: Agricultural productivity is dictated by water availability and consequently drought is the major source of crop losses worldwide. The phytohormone abscisic acid (ABA) is elevated in response to water deficit and modulates drought tolerance by reducing water consumption and inducing other drought-protective responses. The recent identification of ABA receptors, elucidation of their structures and understanding of the core ABA signaling network has created new opportunities for agrochemical development. An unusually large gene family encodes ABA receptors and, until recently, it was unclear if selective or pan-agonists would be necessary for modulating water use. The recent identification of the selective agonist quinabactin has resolved this issue and defined Pyrabactin Resistance 1 (PYR1) and its close relatives as key targets for water use control. This review provides an overview of the structure and function of ABA receptors, progress in the development of synthetic agonists, and the use of orthogonal receptors to enable agrochemical control in transgenic plants.